Covid-19 crisis’ consumer impact: developing an adaptive decision-making model - Suddin Lada; Mohamad Isa Abd. Jalil; Joehan Joehari William; Pg Mohd Faezul Fikri Ag Omar (Penerbit UMS, 2020)
The spread of and reaction to COVID-19 has made our families, organizations, and buyers everywhere are attempting to guarantee that they can adapt to this troublesome time. Everyone must comprehend the seriousness of the outbreak and the extraordinary threat to life posed by COVID-19. Since the movement control order (MCO) was enforced the buying behavior of the average Malaysian has changed. A lot of changes in how people consuming goods and services, forcing retailers to think out of the box to engage with customers. Consumer decision-making, buyer dynamic, and conduct change will quickly adjust dependent on a scope of individual and logical qualities. Our reasoning and arranging about how to explore the world can't depend as much on programmed practices. More than ever, this unprecedented situation has led us to focus on and re-evaluate the existing decision-making model. Therefore, the main objective of this study is to develop an adaptive customer decision-making model focused on the current situation of the outbreak. How have these changes in consumer behavior affected purchasing behavior? How do individuals, families, and businesses react? Building an adaptive decision-making model is significant as the current outbreak situation revealed new and unfamiliar variables and ready for new validation.